A Humanização enquanto componente da formação em saúde: a visão de discentes de graduação - Braz, Maria Gicarlia (2017)
The objective of this study was to identify, from the undergraduate of health area students' point of view, the contribution to their training, experienced in the practices of the project of humanized care to women and children, realized from 2010 to 2013.This was an exploratory, descriptive study with a qualitative approach, in which the unstructured interview technique was used to collect the data. As subjects of the research, there were 14 students from different undergraduate courses of the Federal University of Alagoas and the Center of Higher Education of Maceió. The interpretation of the interviewees' speeches was guided by the Content Analysis Theory of Bardin, as a tool for analyzing the qualitative data. The results indicate that the project in question contributes to the formation of future reflective and critical professionals with the appropriate profile to act in the Unified Health System. It is concluded that, the insertion of the students in humanized extension actions, can result in the formation of Subjects involved in the transformation of health practices, adding new values that allow the construction of new ways of caring in their future professional practice.